A Rare Case of Pancreatic Actinomyces. Issue 1 (20th January 2023) - Poche, Marguerite; Liu, Kyle; Pham, Codey; Jain, Shilpa; Sealock, Robert
ABSTRACT: Actinomyces israelii is a filamentous, gram-positive anaerobic bacterium commonly found in the upper gastrointestinal tract, colon, and female genital tract. Rarely, actinomycosis can infect the pancreas most commonly after pancreatic instrumentation, often mimicking malignancy. We describe a case of a 26-year-old woman who presented with epigastric abdominal pain and nausea without prior pancreatic instrumentation. Abdominal imaging demonstrated a mass in the pancreatic head with fine-needle biopsy revealing Actinomyces . The patient was successfully treated with long-term antibiotic therapy resulting in resolution of the mass. Our case emphasizes the importance of considering nonmalignant etiologies in the differential diagnosis of pancreatic masses.